INVESTIGATING LONG-TERM SIDE EFFECTS OF SNRI: VENLAFAXINE, DULOXETINE, DESVENLAFAXINE, MILNACIPRAN, AND LEVOMILNACIPRAN ANTIDEPRESSANTS TREATMENT IN PATIENTS DIAGNOSED WITH DEPRESSION - Olivia Grygorcewicz; Marta Czachorowska; Franciszek Szweda; Tomasz Poczwardowski; Adrianna Kaczmarek; Katarzyna Anna Kowalska; Jakub Tomasz Latos; Marcin Chwalczuk; Marta Koneczna; Karolina Alicja Krystyniak; Kinga Augustyniak (International Journal of Innovative Technologies in Social Science, 2026)
Depression is a prevalent mental health disorder affecting approximately 4% of the global population. Pharmacological management commonly involves the use of serotonin–norepinephrine reuptake inhibitors (SNRIs), including venlafaxine, duloxetine, desvenlafaxine, milnacipran, and levomilnacipran. Although these agents are effective in alleviating depressive symptoms, their prolonged use raises concerns regarding long-term safety. Clinical guidelines recommend antidepressant (AD) therapy for at least six months following symptom remission after the first episode of major depression; however, in practice, treatment duration often extends for years. Extended exposure to SNRIs has been associated with both common short-term adverse effects—such as weight gain, appetite changes, and sexual dysfunction—and less understood long-term outcomes, including metabolic, cardiovascular, and skeletal complications. The objective of this study is to systematically evaluate existing literature on the long-term side effects of SNRI therapy in patients diagnosed with depression. By synthesizing current evidence, this review aims to enhance understanding of the risk profile associated with chronic SNRI use and inform safer clinical practices.